Identifying central symptom clusters and correlates in children with acute leukemia undergoing chemotherapy: a network analysis - Fang, Jia; Wong, Cho-Lee; Liu, Chun-Qin; Huang, Hai-Ying; Qi, Yi-Shu; Xu, Li-Ling; Wang, Mei-Xiang; Lin, Yan (Frontiers in Oncology, 2023)
Background: Previous studies have examined symptom clusters in children with acute leukemia, yet a knowledge gap persists regarding central symptom clusters and their influencing factors. By identifying these central clusters and associated factors, healthcare providers can enhance their understanding and effective management of symptoms. Our study seeks to address this gap by identifying symptom clusters, exploring central clusters, and investigating the demographic and healthrelated factors associated with these clusters in children with acute leukemia undergoing chemotherapy. 2 This is a provisional file, not the final typeset article Methods: A total of 586 children with acute leukemia from January 2021 to April 2023 were recruited from China. They were investigated using Memorial Symptom Assessment Scale 10-18 during chemotherapy. The principal component analysis was used to identify the symptom clusters. An association network was conducted to describe the relationships among symptoms and clusters. A multiple linear model was used to investigate the associated factors for the severity of overall symptoms and each symptom cluster.Results: Five clusters were identified, including oral and skin cluster, somatic cluster, self-image disorder cluster, gastrointestinal cluster and psychological cluster. Gastrointestinal cluster was the most central symptom cluster. Age, sex, clinical classification, number of having chemotherapy and education degree and marital status of the primary caregiver are associated with the severity of these five symptom clusters.Our study highlights the importance of evaluating symptom clusters in children with acute leukemia during chemotherapy. Specifically, addressing gastrointestinal symptoms is crucial for effective symptom management and overall care.